Coaches` ability to support elite and adolescent soccer players throughout their menstrual cycle - Donnelly, J.; Macrae, E.; Valentin, S.; White, A.; Easton, C.; Forrest, L. J. (International Journal of Sports Science & Coaching, 2024)
Female soccer players report that the menstrual cycle (MC) can negatively impact sporting performance, with barriers identified in communicating their MC experiences to coaches and support staff. Whilst research is growing, there are few studies exploring the coaching staff perspective in soccer, and none from those at the youth level. The aim was to explore soccer coaches` awareness, perceptions and experiences of the MC and the perceived impact on performance. Thirteen coaches (female n = 4; male n = 9, aged 33 ± 9 years) from Scottish elite adult and youth soccer participated in individual semi-structured interviews (average interview time 39 ± 11 min). Interviews were audio recorded and transcribed verbatim, with reflexive thematic analysis (RTA) performed. RTA generated three key themes from 232 meaning units: environment and culture, coach-athlete dynamic, and coach support and education. Coaches perceived a societal culture of the MC being hidden, or taboo, with similar barriers noted within the club environment. Coaches were often embarrassed to discuss the MC with players and believed players were embarrassed. Communication differed depending on the coach-athlete relationship, with trust and familiarity cited as improving comfort in communication. Coach awareness and understanding of the MC both generally and within a sporting context influenced their perceived ability to communicate and support players. Findings highlight the need to support coaches by providing MC education, and practical guidance on how to support players` health and wellbeing. Improved confidence in communication should allow players to feel supported and normalise conversations about the MC.